Assessment of synechococcus sp. and pseudanabaena sp. cell culture model system for biogenesis and heavy metal sequestration mechanism - Othman, Rashidi; Shaharuddin, Ruhul Izzati; Wan Sulaiman, Wan Syibrah Hanisah; Hj. Baharuddin, Zainul Mukrim (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Water pollution and water scarcity due to the discharge of untreated domestic and industrial wastewater into aquatic bodies need serious attention. A number of physical, chemical, and biological methods have been developed for wastewater treatment; among these, the use of cyanobacteria is considered as sustainable ways of averting the consequences. The dual application of microalgae for phycoremediation and biomass production for value products like biofuels and fertilizers is a feasible and eco-friendly alternative. This research aimed to investigate variables controlling heavy metal sequestration mechanism by assessing the effects of environmental variables from the mixtures of artificial wastewater samples using Synechococcus sp., and Pseudanabaena sp. Six heavy metals (Pb, Fe, Cr, Cd, Al, and Cu) treatments were tested and analyzed by Inductively Coupled Plasma (ICP) at three different periods of time (week 1 until week 3). The results indicated that both cyanobacteria species have equal potential to sequester heavy metals. However, Pseudanabaena sp. is the best phycoremediator agent due to substantial high Bioconcentration factor (BCF) compared to Synechococcus sp. On top of that, a regulatory step for the cyanobacteria cell growth and production mechanism is mediated by pH.